2022
DOI: 10.14569/ijacsa.2022.0130948
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Noise Removal Techniques on Retinal Optical Coherence Tomography Images

Abstract: In the biomedical field, automatic disease detection by image processing has become the norm in the current days. For early illness detection, ophthalmologists have explored a variety of invasive and noninvasive procedures. Optical Coherence Tomography (OCT) is a noninvasive imaging technique for obtaining high resolution tomographic images of biological systems. The image quality is degraded by noise, which degrades the performance of noisy image processing algorithms. The OCT images captured with speckle noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…De-noising techniques that successfully eliminate speckle noise. Many authors suggested bilateral filtering technique and wiener filtering approach [31][32][33][34][35][36] satisfies this condition. Different filtering methods were used to eliminate the speckle-noise in the OCT images.…”
Section: B Pre-processingmentioning
confidence: 99%
“…De-noising techniques that successfully eliminate speckle noise. Many authors suggested bilateral filtering technique and wiener filtering approach [31][32][33][34][35][36] satisfies this condition. Different filtering methods were used to eliminate the speckle-noise in the OCT images.…”
Section: B Pre-processingmentioning
confidence: 99%
“…where An extracted speckle noise should be added to the simulated B-scan using the mathematical A-scan (MA_line) and least-square-fit A-scan (LS_line); the frames simulated by the real average A-scan (RA_line) already have the speckle noise. To extract the speckle noise, the MATLAB median and Wiener filter can be used [52]. Figure 7 shows a median and Wiener filter applied on the original demineralized OCT frame with kernel windows of 3 × 3 and 5 × 5, respectively.…”
mentioning
confidence: 99%